Persepsi Penyedia dan Pemakai Laporan Keuangan Terhadap Pengungkapan Biaya Riset dan Pengembangan - Nur Sayidah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
The main purpose of this study is to examine the cost and benefit on disclosures of the research and development (R&D) costs by comparing the perceptions of financial managers (prepares of financial statement) and financial analysts (users of financial statement). Stated hypotheses to examine were: first, differences of the perceived net cost or net benefit of disclos¬ing research and development expenditures both mandatory disclosures or voluntary disclosures. Second, perceptions’ differences on the magnitude of costs/disadvantages which constrain R & D costs disclosures.Data collection was carried out by a questionare survey. Respondents are financial managers from manufacturing firms and financials analysts from security houses. The method were used to test the stated hypotheses is t-test.The result shows that: first, there are no significant differences in the perceptions of fi¬nancial managers and financial analysts about net benefit or net cost of disclosing R & D costs. Second, there are significant differences in the perceptions of financial managers and financial analysts about magnitude of collecting and processing cost and auditing cost. Keywords: disclosure, research and development costs, net benefit, net cost